Drivers and Health Impacts of Ambient Air Pollution in Slovakia - World Bank (World Bank, Washington, DC, 2021)
This report, created with the support of the Structural Reform Support Program of the European Commission (EC), provides an estimate of the health impacts of current concentrations of air pollutants in the Republic of Slovakia across its 72 districts (the two biggest cities are counted as one each) and evaluates the benefits of measures to reduce concentrations of pollutants relative to the costs of such measures. At the same time, a toolkit is prepared so that similar analyses can be conducted in the future. The study is motivated by the need to better understand the extent of the health consequences of the levels of ambient air pollution in Slovakia (which is among the highest in Europe) and to evaluate different actions to improve air quality in terms of their benefits relative to their costs. In this way policy actions to address air pollution can be more cost effective.